SHARED LEADERSHIP DALAM MEMBANGUN KOMITMEN ORGANISASI DI DINAS PARIWISATA DAN EKONOMI KREATIF DKI JAKARTA - Putri Allana Abdullah (MANAJEMEN, 2023)
This study aims to analyze the effect of shared leadership on organizational performance by considering the role of organizational commitment as a mediating variable and the role of government as a moderating variable. This study was conducted at the DKI Jakarta Province Tourism and Creative Economy Office. The sampling technique used was simple random sampling, the number of samples was 105 respondents, and hypothesis testing used the SMART-PLS software tool. The results showed that shared leadership has a positive and significant impact on improving organizational performance through strengthening organizational commitment. Employees who are actively involved in decision making and work collaboratively tend to show better performance. On the other hand, the role of government in supporting the strengthening of shared leadership is still not optimal due to the lack of cross-sectoral coordination and limitations in effective policy management. Therefore, increasing human resource capacity and more integrative policy strategies are needed to ensure the sustainability of the tourism sector. With good synergy between leadership, organizational commitment, and government policies, it is hoped that the performance of the DKI Jakarta Tourism and Creative Economy Office can further improve